Implementation of the Constructivist Approach in the Advanced History Learning Process at SMAN 1 Alalak - Riyanni, Riyanni; Prawitasari, Melisa; Sriwati, Sriwati (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2026)
Teachers as those in control of the learning process should implement an approach that fully supports students. However, learning is often teacher-centered leaving students passive, especially in advanced history subjects. This study aims to analyze the planning, implementation and assessment of advanced history learning at SMAN 1 Alalak using a constructivist approach. The research method is a qualitative case study with data collection techniques including interviews, observations and documents. The results show that teachers design plans that can make students active in learning. During the learning process, teachers act as facilitators and students construct knowledge based on their cognitive abilities and through social interactions with teachers and peers. Assessment of the learning process is carried out using formative and summative assessments to identify students' needs, development and learning outcomes. Based on this, the implementation of the learning process at SMAN 1 Alalak using a constructivist approach is running very well.